2001
DOI: 10.1046/j.1471-4159.2001.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acid residues responsible for the α5  subunit binding selectivity of L‐655,708, a benzodiazepine binding site ligand at the GABAA receptor

Abstract: L-655,708 is a ligand for the benzodiazepine site of the g-aminobutyric acid type A (GABA A ) receptor that exhibits a 100-fold higher af®nity for a5-containing receptors compared with a1-containing receptors. Molecular biology approaches have been used to determine which residues in the a5 subunit are responsible for this selectivity. Two amino acids have been identi®ed, a5Thr208 and a5Ile215, each of which individually confer approximately 10-fold binding selectivity for the ligand and which together account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 18 publications
3
52
0
Order By: Relevance
“…2G Inset) and increased the charge transfer of the mIPSCs to 132.7 Ϯ 6.2% of control (n ϭ 15, P Ͻ 0.05). Binding studies showed that L-655,708 exhibits at least a 50-fold selectivity for ␣5␤2␥2 GABA A Rs compared with heteromeric complexes containing ␣1, ␣2, ␣3, or ␣6 subunits (31,32). Application of L-655,708 (5 M and 50 M; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2G Inset) and increased the charge transfer of the mIPSCs to 132.7 Ϯ 6.2% of control (n ϭ 15, P Ͻ 0.05). Binding studies showed that L-655,708 exhibits at least a 50-fold selectivity for ␣5␤2␥2 GABA A Rs compared with heteromeric complexes containing ␣1, ␣2, ␣3, or ␣6 subunits (31,32). Application of L-655,708 (5 M and 50 M; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To begin to elucidate the structures within the ␣ 5 subunit responsible for this property, we examined amino acid residues previously shown to be important in determining its pharmacological properties. The ␣ 5 subunit is also distinctive in its higher sensitivity to positive modulation by several benzodiazepine derivatives (Liu et al, 1996;Quirk et al, 1996;Strakhova et al, 2000), and an isoleucine residue (I215) in the extracellular domain was identified as important for this characteristic (Strakhova et al, 2000;Casula et al, 2001). This subunit also has a high sensitivity to inhibition by zinc, a property conferred by a unique histidine residue (H195) found only in the ␣ 5 subunit (Fisher, 2002b).…”
Section: Resultsmentioning
confidence: 99%
“…A potential weakness of this argument is that the concentration of L-655,708 used in this study and the study by Caraiscos et al (2004) was deliberately chosen to be higher than the binding affinity for ␣5GABA A Rs (Casula et al, 2001) to maximize the sensitivity of this assay. However, it raises the possibility of nonspecific actions of L-655,708 [although 50 M L,655-708 had no detectable effect in ␣5GABA A R Ϫ/Ϫ mice (Caraiscos et al, 2004) and on the amplitude of sIPSCs in our experiments; p ϭ 0.12].…”
Section: ␣5gaba a Rs Are Recruited By Increasing [Gaba] Omentioning
confidence: 99%